Catalyst/Additive Free Oxidation of Benzyl Bromides to Benzaldehydes. Issue 47 (17th December 2020) - Aman, Hasil; Chen, Yuan‐Ching; Tu, Jing‐Wen; Chang, Chia‐Chi; Chuang, Gary Jing
Abstract: An effective approach for the synthesis of aryl aldehydes from the corresponding benzylbromides was accomplished. Without need of additional additives or stoichiometric oxidants, this environmental friendly and milder version of Kornblum oxidation simply utilized the irradiation of visible light in DMSO under O2, and is compatible with the substrate with different functional groups. Abstract : Herein we report an aerobic oxidation of benzyl bromides under visible light to afford benzaldehydes in moderate to excellent yields. Without the need of additional catalyst or stoichiometric amount of traditional oxidant, this modified version of Kornblum oxidation could be an environmental friendly methodology for the synthesis of benzaldehyde moiety. Based on experimental observations, a plausible mechanism is also proposed.